2017
DOI: 10.1002/mgg3.301
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis ofBRCA1andBRCA2genes in Peruvian families with hereditary breast and ovarian cancer

Abstract: BackgroundBreast cancer is one of the most prevalent malignancies in the world. In Peru, breast cancer is the second cause of death among women. Five to ten percent of patients present a high genetic predisposition due to BRCA1 and BRCA2 germline mutations.MethodsWe performed a comprehensive analysis of BRCA1 and BRCA2 genes by Sanger sequencing and multiplex ligation‐dependent probe amplification (MLPA) to detect large rearrangements in patients from 18 families, which met the criteria for hereditary breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
12
0
2
Order By: Relevance
“…p.L771L, p.S1436S, p.P871L, p.E1038G and p.K1183R has also been reported for other Indian population and among them, p.P871L, p.E1038G and p.K1183R were listed on top 20 BIC entries. There are reports that absence of BRCA1 p.K1183R increases breast cancer risk suggesting the protective effect of the polymorphism [7,24]. The possible hypothesis behind cancer occurrence despite the presence of p.K1183R polymorphism in our studied cases could be the balance between DNA damage and repair that determines the individual susceptibility to breast cancer.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…p.L771L, p.S1436S, p.P871L, p.E1038G and p.K1183R has also been reported for other Indian population and among them, p.P871L, p.E1038G and p.K1183R were listed on top 20 BIC entries. There are reports that absence of BRCA1 p.K1183R increases breast cancer risk suggesting the protective effect of the polymorphism [7,24]. The possible hypothesis behind cancer occurrence despite the presence of p.K1183R polymorphism in our studied cases could be the balance between DNA damage and repair that determines the individual susceptibility to breast cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Except for the novel polymorphism, the remaining polymorphisms have been repeatedly reported to have no clinical significance in BIC BRCA and ClinVar database by several genetics clinics from all over the world and majority of these polymorphisms reported in these repositories are unpublished [7]. p.L771L, p.S694S, p.P871L, p.E1038G, p.K1183R from exon 11 and p.S1436S from exon 13 of BRCA1 gene has been reported by many studies as polymorphisms or variants of uncertain significance with minor allele frequency (MAF) more than 25% [23,24,25]. p.S694S was reported to be associated with age at diagnosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…The alterations found in the sampled population are shared with Spain (c.4308 T > C y c.4837A > G) [37] and some Latin American populations, such as those from Peru (c.2082C > T, c.2311 T > C, c.2612C > T, c.3113A > G, c.3548A > G, c.4308 T > C, c.2229 T > C, c.2971A > G, c.3396 T > G, c.3807 T > C, c.4563A > G) [38], Venezuela (c.4308 T > C, c.4837A > G, c.2229 T > C, c.2971A > G, c.4563A > G, c.6513C > G) [39], Argentina (c.2077 G > A, c.2612 C > T, c.3113A > G c.3548A > G, c.2971A > G) [40, 41], Brazil (c.2082 C > T, c.2368A > G, c.2612 C > T, c.2229 T > C, c.3396 T > G, c.3807 T > C, c.4563A > G, c.6513C > G) [42, 43], Mexico (c.6841 + 80_6841 + 8 3delTTAA) [44] and Chile (c.2311 T > C, c.3113A > G, c.3548A > G, c.2971A > G, c.3396 T > G) [45, 46]; it is important to note, however, that not all studies sequenced the BRCA1 and BRCA2 genes. In addition, most of them used PTT; with this, it is not possible to obtain information about the presence of these polymorphisms in all Latin American populations that have been reported in genetic studies including these two genes.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Vaca-Paniagua et al [81] using pyrosequencing determined a frequency of 41% of BRCA genes alterations in Mexican patients, where 10% were known mutations while the rest were novel or variants with unknown clinical significance. On the other hand, Buleje et al [14] in a comprehensive evaluation of BRCA genes, reported a new mutation in the Peruvian population. It indicates the great need for comprehensive profiling of germline mutations in LATAM with the intention to develop more accurate tests, which are customised for this population.…”
Section: Hereditary Breast Cancermentioning
confidence: 99%